Penerapan Metode Simpleks pada Usaha Dagang Bintang Tiurma - Matheus Supriyanto Rumetna; Tirsa Ninia Lina; Levinson Reza Tauran; Nova Sitorus; Theresia Patty; Albertina Malak; Kristin Yawan; Novela orisu (Politeknik Negeri Cilacap, 2020)
Bintang Tiruma Trade Business is a Trading Business (TB) that is engaged in trade, namely the production of furniture such as minimalist doors and panel doors. Along with business development accompanied by intense competition, many problems arise and also affect TB, one of which is related to the availability of raw materials. Available raw materials have a limited amount that affects the production process. In order to maintain the development of production, it takes several stages in order to allocate raw materials and increase profits. The combination of the simplex method in processing data and the use of POM-QM software for Windows 5.0 for data analysis can be used as a solution in solving this problem. The result is that this method can speed up and simplify the calculation in determining the maximum profit obtained from the sale of minimalist doors and panel doors made within 1 (one) week. In addition, this greatly helps Bintang Tiurma TB to overcome the constraints of the availability of raw materials.